Development of a Bingo Game as a Self-Esteem Stimulation Medium for Senior High School Students - Susmayati Susmayati; Yenti Arsini (Journal of Education and Teaching Learning, 2026)
Low self-esteem remains a common issue among senior high school students, as reflected in low self-confidence, pessimistic attitudes, and difficulties in expressing themselves. These conditions may hinder students’ personal and social development, highlighting the need for innovative guidance and counseling media. This study aimed to develop a bingo-based educational game as a medium for stimulating students’ self-esteem through group counseling services. This research employed a Research and Development (R&D) approach using the 4D model, consisting of the define, design, develop, and disseminate stages. The research subjects included material experts, media experts, guidance and counseling teachers, and eleventh-grade students of SMA Negeri 1 Berastagi. Data were collected using Likert-scale questionnaires and analyzed quantitatively through descriptive percentage techniques to determine the feasibility and acceptability of the developed media. The findings revealed that the bingo game media achieved a feasibility score of 96.42%, indicating a “highly feasible” category. In addition, teacher and student responses reached 94.94%, categorized as “strongly agree.” These results demonstrate that the developed bingo game is highly appropriate and well accepted as a medium for stimulating students’ self-esteem within guidance and counseling services.